The potential impacts of human genetics on virus emergence - Ryan A. Langlois; Jean-Laurent Casanova (Proceedings of the National Academy of Sciences, 2025)
Human monogenic traits can confer resistance to viral infection in exposed individuals or predisposition to severe disease in infected individuals. Enhanced susceptibility can be driven directly by mutations in genes essential for control of the virus or indirectly via the production of autoantibodies against components of host defense. While the impact of viruses on individuals carrying these genotypes permitted their identification and has been amply studied, little is known about the impact of these human genotypes on the natural history of viruses, including not only persisting but also emerging viruses. We envisage several scenarios, including the possibility that genetically susceptible individuals serve as patient zeros, superspreaders, or mutation incubators, or that genetically resistant individuals even permit the selection of new viral mutants. Viruses are continually shared between individuals and even host species, where they can benefit from adaption to new environments. Current human viruses, as well as novel viruses from animal reservoirs, will continue to threaten the human population. Improvements in the scale of human genomic sequencing and analysis will permit testing hypotheses about the impact of human genetics on the origin and trajectory of viral infections, including future pandemics, which may ultimately help to prevent or curtail impending outbreaks.